Microbial mechanisms of tolerance to weak acids: an overview - Nuno Pereira Mira (Frontiers Research Topics, 2014)
Carboxylic acids are ubiquitous molecules found in microbial metabolic pathways and that have been explored for a wide array of applications including food preservation (e.g., acetic, propionic, benzoic, and sorbic acids), chemotherapy (e.g., the analgesic acetylsalicylic acid, the immunosuppressor mycophenolic acid or the antimalarial drugs artesunic and artemisinic acids) or agriculture (e.g., the herbicides 2,4-dichlorophenoxyacetic acid). This Research Topic contributes to the understanding of the molecular mechanisms underlying adaptation to weak acid stress in microbes, a knowledge base that impacts the fields of Medicine, Health, Food Safety and the Environment.